Simultaneous carbon footprint allocation and design of trigeneration plants using fuzzy fractional programming - Ubando, Aristotle T. (Animo Repository, 2013)
Trigeneration systems offer an inherently efficient, low-carbon approach to producing useful energy streams. Due to multiple products from a trigeneration system, the challenge of allocating carbon footprint to each energy stream arises, particularly if the streams are sold to different customers. A fuzzy fractional programming model is proposed to design a trigeneration system, taking such allocation into account. The model allows for solving for a configuration that gives the minimum carbon footprint for each energy stream, given a range of values for demand for each product in a trigeneration system. The final design must meet a specified energy output requirement, while satisfying fuzzy carbon footprint limits for all products. The methodology is illustrated using hypothetical but realistic case studies. Sensitivity analysis was carried out to show the effects of changing the system carbon footprint limits. © Springer-Verlag Berlin Heidelberg 2012.